PELAYANAN PUBLIK BIDANG PERIZINAN: STUDI PADA PEMBUATAN SURAT IZIN MENGEMUDI (SIM) C DI SATUAN PENYELENGGARAAN ADMINISTRASI KECAMATAN TUALANG KABUPATEN SIAK TAHUN 2022 - Jubaidah, Ade; ,, Adlin (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
Service activities are the process of fulfilling service needs in accordance with the Law. Public services can be categorized as effective if the public gets easy service with short, fast, and precise satisfying procedures. The succes public of services is determined by the government's ability to improve the work discipline of service officers. In the Regulation of the Chief the Republic of Indonesia National Police Number 9 of 2012 Article 52 Paragraph 2 Concerning Driving Licenses, it is stated that the authority to issue SIM to the public is the Chief of Police in each respective region and is delegated to the Head of the Traffic Unit. The large number of people who not have a driving license when the Tualang District Police conducted a raid makes this matter need more attention from the Tualang District Satpas, are there any things in the service that make people not have a license when riding a motorbike. This study uses a Descriptive research method with a qualitative approach. This study use the theory of the principles of public service according to Dr.Drs.Ratminto,m.pol.admin, where there are principles that must be considered in the implementation of government services and licensing, namely: 1) Empathy, 2) procedural limitations, 3) clarity of service procedures, 4) minimizing requirements, 5) clarity of authority, 6) transparency of costs, 7) certainty of schedule, 8) validity period of permits, 9) clarity of rights and authorities and 10) complaint handling, according to the author's analysis based on the results of the study, the implementation of public services at the Tualang District Satpas has been fairly good, all of these points have been running quite well according to the theory of the principles of public service, but there are still several aspects that will be a reference for making changes to improve. Keywords: Public services, Licensing, Driving License